Imaging in Suspected Cardiac Sarcoidosis: A Diagnostic Challenge - Ha, Francis J.; Agarwal, Sharad; Tweed, Katharine; Palmer, Sonny C.; Adams, Heath S.; Thillai, Muhunthan; Williams, Lynne (Current Cardiology Reviews, 2020)
Cardiac Sarcoidosis (CS) represents a unique diagnostic dilemma. Guidelines have been recently revised to reflect the established role of sophisticated imaging techniques. Trans-thoracic Echocardiography (TTE) is widely adopted for initial screening of CS. Contemporary TTE techniques could enhance detection of subclinical Left Ventricular (LV) dysfunction, particularly LV global longitudinal strain assessment which predicts event-free survival (meta-analysis of 5 studies, hazard ratio 1.28, 95% confidence interval 1.18-1.37, p < 0.0001). However, despite the wide availability of TTE, it has limited sensitivity and specificity for CS diagnosis. Cardiac Magnetic resonance Imaging (CMR) is a crucial diagnostic modality for suspected CS. Presence of late gadolinium enhancement signifies myocardial scar and enables risk stratification. Fluorodeoxyglucose Positron Emission Tomography (FDG-PET) coupled with myocardial perfusion imaging can identify active CS and guide immunosuppressant therapy. Gallium scintigraphy may be considered although FDG-PET is often preferred. While CMR and FDG-PET provide complementary information in CS evaluation, current guidelines do not recommend which imaging modalities are essential in suspected CS and if so, which modality should be performed first. The utility of hybrid imaging combining both advanced imaging modalities in a single scan is currently being explored, although not yet widely available. In view of recent, significant advances in cardiac imaging techniques, this review aims to discuss changes in guidelines for CS diagnosis, the role of various cardiac imaging modalities and the future direction in CS.
Keywords: LV dysfunction